Blurring the Paradigmatic Edges: Navigating the Boundaries Between Critical-Interpretive and Interpretive Approaches to Health Communication Research - Kerber, Anne (Frontiers in Communication, 2019)
Critical-interpretive health communication (CIHC) scholars take seriously the imperative to “take an ethical position” on communicative phenomenon, specifically identifying both issues of power as well as opportunities to catalyze social change (Zoller & Kline, 2008, p. 93) Yet, researchers are also likely to encounter competing impulses to understand or even appreciate others’ lived experiences in line with interpretive health communication (IHC) practices. My perspective essay traces the blurry edges between CIHC and IHC, and offers guidance to researchers who traverse these borders. Specifically, I articulate the key points of convergence and divergence between CIHC and IHC perspectives, and consider the questions and implications accompanying these approaches.